Leveraging the Multiple Lenses of Psychological Science to Inform Clinical Decision Making: Introduction to the Special Section. (March 2018) - Marsh, Jessecae K.; De Los Reyes, Andres; Lilienfeld, Scott O.
Understanding how clinicians and laypeople make critical decisions related to the assessment, diagnosis, and treatment of mental health is an important step toward improving mental healthcare. This Special Section features new research that, collectively, leverages interdisciplinary approaches from basic psychological science to enhance our understanding of clinical decision making. In this "Introduction to the Special Section, " we illustrate how three tasks integral to clinical decision making (assessment, diagnosis, and treatment selection) can be reframed as specific examples of more basic cognitive processes. We conclude by highlighting challenges to conducting interdisciplinary research on clinical decision making, by providing an overview of the contributions in this Special Section, and by presenting a list of essential readings on clinical decision making.